Timing of First Respiratory Virus Detections in Infants: A Community-Based Birth Cohort Study - Sarna, Mohinder; Ware, R.; Lambert, S.; Sloots, T.; Nissen, M.; Grimwood, K. (Oxford University Press, 2018)
© 2017 The Author(s). Background. Determining timing of first virus detection episodes (fVDEs) for different respiratory viruses in infants identifies risk periods and informs preventive interventions, including vaccination. We describe the ages and nature of fVDEs in an infant birth cohort and explore factors associated with increased odds of symptomatic fVDEs. Methods. The Observational Research in Childhood Infectious Diseases (ORChID) study is a community-based birth cohort describing acute respiratory infections in infants until their second birthday. Parents recorded daily symptoms and collected nose swabs weekly, which were batch-tested using polymerase chain reaction assays for 17 respiratory viruses. Results. One hundred fifty-eight infants participated in ORChID. The median age for fVDEs was 2.9 months for human rhinovirus (HRV) but was =13.9 months for other respiratory viruses. Overall, 52% of HRV fVDEs were symptomatic, compared with 57%.83% of other fVDEs. Respiratory syncytial virus and human metapneumovirus fVDEs were more severe than HRV fVDEs. Older age and the winter season were associated with symptomatic episodes. Conclusions. Infants do not always experience respiratory symptoms with their fVDE. Predominance of early HRV detections highlights the need for timing any intervention early in life. fVDEs from other respiratory viruses most commonly occur when maternal vaccines may no longer provide protection.